NEW HIGH-TECH METHODS OF RHEOLOGICAL PROPERTIES EVALUATION IN CHEESEMAKING: STUDY OF MILK COAGULATION AND FORMATION OF CHEESE CURD STRUCTURE - Mayorov A.A. (Техника и технология пищевых производств, 2017)
The coagulation of milk mixture is an important technological stage of cheese-making. Peculiar features of curd formation affect the choice of cheese-making conditions and determine the quality of cheese. At the Siberian Research Institute of Cheese- making two instruments and two methods allowing monitoring of milk coagulation process and rheological properties of curd formation have been developed. The methods allow us to investigate the dynamics of milk coagulation and to measure the rheological characteristics of the curd (strength and elasticity). The first method and the instrument are designed to study the effect of conditions of milk mixture coagulation and curd treatment. The advantage of this method is the possibility of obtaining undistorted curd in the vessel which is then transferred to the device for measuring strength tensile. The device allows making comparative experiments on the same milk sample changing the factors (dose of enzyme, pH, and mass fraction of solids). The second instrument is a modernized version of a reconciler and has been designed to measure the ultimate strength. The ultimate strength of cheese curd reflects its technological properties and correlates with the loss of the cheese mass in the development of cheese curd. Analyzing the dynamics of formation of curd rheological characteristics it has been established that ultimate strength is not always a function of time: in many cases local extremes are observed. This phenomenon depends on the kind of milk coagulating enzyme, the protein composition of milk, the concentration and the state of calcium ions, the presence of inhibitory substances in milk. The developed methods make enable us to adjust processing at early stages of cheese-making, to specify binding properties of the cheese mass and the losses of milk components. The instruments and methods can be used more effectively when making cheese from mixtures which include dry and condensed components.